Colorimetric Estimation of Acenocoumarol in Bulk and Pharmaceutical Formulations - Ankita, M.; Gurupadayya, B.M.; Chandra, Akhilesh (Asian Journal of Chemistry, 2010)
Two simple spectrophotometric methods for the analysis of acenocoumarol in pure form and in pharmaceutical formulation have been developed. Method A is based on diazotization of amino group of reduced acenocoumarol with nitrous acid followed by its coupling with N-(1-naphthyl)ethylenediamine-dihydrochloride (BMR) reagent in presence of ammonium sulphamate to form a blue colour chromogen and maximum absorbance at 565 nm. Beer's law is obeyed in the concentration range of 4-14 μg/mL. Method B is based on amino group of reduced acenocoumarol forms a condensation product with Gibb's reagent (2,6- dichloroquinone-4-chlorimide) and the maximum absorbance at 544 nm. Beer's law is obeyed in the concentration range of 4-20 μg/mL. The methods have been statistically evaluated and are found to be precise and accurate. The results obtained are reproducible with coefficient of variation less than 1 %.